Denominative and Deverbal Suffixes in Kökşetav Copy of Divân Hikmet - Utebekov, S.B. (Journal of Oriental Studies, 2022)
Denominative and deverbal suffixes in the historical texts of Turkish are rich both in terms of number and their functions. We encounter different functions of denominative and deverbal suffixes which is main subject of our article in the Kökşetav (Kazakhstan) copy of Divân-ı Hikmet. We confirmed nearly twenty suffixes like {+Aç}, {+An}, {+çI}, {+dAş}, {+ĠA}, {+ĠU}, {+lIḳ}, {+lUĠ}, {+nçI}, {+mAn}, {+sIz}, {+rAḲ}, {-AḲ/ -Ḳ}, {-(U)Ḳ/ -(I)Ḳ}, {-(U)Ġ/ -(I)Ġ}, {-ĠAn}, {-ĠUçI}, {-ĠUlUĠ}, {-ḲUn}, {-ş}etc. in the text. In generally these suffixes have the same phonetic features with Chagatai Turkish but besides that we can see the traces of these suffixes not only in Old Turkish but also in contemporary Turkish Dialects. Therefore, we can regard these suffixes as a follow-up of suffixes which were used before Chagatai period. In the article, these issues will be examined in detail.